Stroke-induced immunodepression: consequences, mechanisms and therapeutic implications. (September 2008) - Meisel, Andreas; Meisel, Christian
The clinical picture of stroke is not only characterized by neurological deficits but also by the high incidence of infectious complications, in particular pneumonia. The occurrence of pneumonia in stroke patients is associated with higher mortality, larger neurological deficits, longer hospitalization and increased costs for medical care. Immobilization and impaired protective reflexes are known to increase the risk of aspiration pneumonia. However, recent experimental and clinical evidence indicates that stroke-induced immunodepression is an independent risk factor that increases susceptibility to infections. This review provides an update on the mechanisms and consequences of stroke-induced immunodepression. The growing insight into these mechanisms may allow new immunomodulatory treatment approaches in stroke patients in the future. In the meantime, several trials on preventive antibacterial treatment to reduce the incidence of post-stroke infections have been conducted, which will be summarized in this review.